The Effectiveness of Police Intelligence in Handling Mining-Related Crimes: Evidence from Kutai Kartanegara (2023-2025) - Redika Adytia Silalahi; Surya Nita; Sylvia Prisca Delima (Transpublika Publisher, 2026)
Illegal mining remains one of the most persistent criminal challenges in Kutai Kartanegara, marked by recurring hotspots, organized operations, and frequent use of heavy machinery. Police records from 2023–2025 show fluctuating yet consistently high activity, totaling twenty cases. While several cases advanced to Stage II (P21) and were transferred to the District Attorney, many remained at the inquiry stage, revealing weaknesses in intelligence detection, evidence gathering, and identification of broader criminal networks. This study examines how police intelligence investigations are conducted, the operational challenges encountered, and the effectiveness of intelligence-led policing against illegal mining. Using qualitative field research, the study combines non-participatory observation and semi-structured interviews with key officials, including the heads of the Criminal Investigation Unit, Intelligence Unit, and General Crime Sub-Unit. Primary field data are supported by police documents, regulations, and previous academic literature, then analyzed through descriptive qualitative methods and triangulation. Findings show strong tactical capability in detecting active sites and advancing cases to Stage II. However, major limitations persist: difficult access to remote areas, limited surveillance technology, weak inter-agency coordination, and difficulty mapping networks beyond field operators. Consequently, illegal mining repeatedly occurs in the same locations, indicating current intelligence practices are insufficient for long-term prevention. Strengthening analytical capacity, improving technological support, and enhancing collaboration are essential to increase enforcement effectiveness.